Incorporating new age technology into campus lighting - Matlack, Daniel W. (Kansas State University, 2009)
Sustainable design and green engineering practices have become a priority in the architectural design industry over the past few years. Energy codes and standards have become more stringent as energy costs rise and buildings become larger, consuming more energy and having a larger impact on the environment. One major area for improvement to meet these new requirements is in the lighting area. Kansas State University (KSU) in Manhattan, KS has had the same campus walkway lighting system for over 50 years and it does not meet the current energy codes and standards. This paper will perform a case study of the current walkway lighting system on the KSU campus, specifically focusing on the Quad area and applying the same principles to the entire campus. The illumination and fixture distribution characteristics will first be established and analyzed to determine an accurate baseline for later comparison. Issues regarding the illumination, efficiency, aesthetics, maintenance, and landscaping will be addressed once the current conditions are established. Lighting technology has changed dramatically in the past year with the development of high efficiency fluorescent, induction, and light emitting diode (LED) lighting. New LED technology has proven to be the most efficient and has been adapted to create outdoor LED fixtures that could help KSU surpass the current energy standards and improve the overall quality of light to correct some of the current issues the existing lighting creates. A full analysis of the illumination, efficiency, aesthetics, and economic feasibility will be performed. The economic analysis will compare existing maintenance and energy costs to that of the first-cost with maintenance, and energy costs to determine an estimated payback. Once the analysis is complete, future options for KSU to implement new lighting technology will be discussed. By creating a more environmentally conscious campus, using high efficiency lighting, KSU could set an example for other universities to pursue sustainable technology and design.
Keywords: Light Emitting Diode- LED; Campus lighting; Scotopic; Photopic; Light Loss Factor-LLF; Sustainable; Architecture (0729); Engineering, Electronics and Electrical (0544)